Interpretasi Letak Bidang Longsor dan Faktor Aman Lereng dengan Bahasa Pemrograman MATLAB - Anita Widianti, Joko Supriyadi , (Jurnal Semesta Teknika, 2011)
Slope stability analyses can be performed using computer program, such as Matrix Laboratory (MATLAB). In the current work, a computer program for slope stability analysis named JOZLOPE based on MATLAB and using Bishop simplified analysis method was used to determine the location of a slip surface and its safety factor. The validation is carried out by analyzing three simple slope models and comparing their results by JOZLOPE and some comparator slope stability analysis programs. It is found that the variations between JOZLOPEâs results and those of the comparators are less than 1% for bottom circle-slope geometry intersection, less than 7% for top circle-slope geometry intersectionÂ and less than 4% for Safety Factor. These findings demonstratesÂ that the a MATLAB program is successfully compiled and it produced measured values that agree with those of their respective comparator.Â Â